A Method of Evaluating the Destruction of a Reinforced Concrete Hollow Core Slab for Ensuring Fire Resistance - Sidnei S. O.; Nuianzin O. M.; Kostenko T. V.; Berezovskyi A. I.; Wąsik W. (Журнал інженерних наук)
Fire tests of reinforced concrete floor slabs do not allow the detection of the onset of the boundary state due to loss of entirety because blocks are installed on the unheated surface to reproduce the design load. This prevents the formation of cracks through which toxic combustion products, smoke, and temperature spread can penetrate. Determining a building structure’s actual fire resistance limit was fixed at the onset of any fire resistance boundary state. It was proven that calculation methods for fire resistance assessment have significant advantages over experimental methods. To reduce the number of finite elements for a rational calculation of the fire resistance assessment of a reinforced concrete hollow core slab, a geometric model of 1/4 of this structure was built. The possibility of visualizing the studied structure at full scale was realized when obtaining the calculation results. The stress-strain state of the studied structure was evaluated based on the thermal and mechanical loading results applied to the reinforced concrete hollow core slab. Thus, the work’s objective was achieved based on the calculation experiments’ results. A methodology was developed for calculating the destruction of a reinforced concrete hollow core slab while assessing its fire resistance. Scientific fundamentals for determining the onset of the boundary state of loss of entirety were developed. The proposed methodology allowed for a reliable assessment of the fire resistance of such structures.